2022
DOI: 10.1007/s40572-022-00353-9
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics at the Intersection of COVID-19 Risk and Environmental Chemical Exposures

Abstract: Purpose of Review Several environmental contaminants have been implicated as contributors to COVID-19 susceptibility and severity. Immunomodulation and epigenetic regulation have been hypothesized as mediators of this relationship, but the precise underlying molecular mechanisms are not well-characterized. This review examines the evidence for epigenetic modification at the intersection of COVID-19 and environmental chemical exposures. Recent Findings Numerous environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 136 publications
0
5
0
Order By: Relevance
“…Given the potential sensitivity of the developing immune system to early phthalate exposure, researchers have called for critical policy reforms and stricter regulations on phthalates such as DEHP to protect healthy development in children. The limited evidence on potential biological mechanisms through which phthalates may adversely affect immune system development may be one of the reasons that these chemicals are still considered safe exposures for pregnant women and children [80,81]. This was the first study to examine infant epigenetic age as a potential biomolecular mediator of the immunosuppressive effects of prenatal exposure to DEHP, and future well-powered investigations are needed to replicate and validate the present findings.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Given the potential sensitivity of the developing immune system to early phthalate exposure, researchers have called for critical policy reforms and stricter regulations on phthalates such as DEHP to protect healthy development in children. The limited evidence on potential biological mechanisms through which phthalates may adversely affect immune system development may be one of the reasons that these chemicals are still considered safe exposures for pregnant women and children [80,81]. This was the first study to examine infant epigenetic age as a potential biomolecular mediator of the immunosuppressive effects of prenatal exposure to DEHP, and future well-powered investigations are needed to replicate and validate the present findings.…”
Section: Discussionmentioning
confidence: 76%
“…A recent epigenome-wide investigation indicated that prenatal exposure to phthalates may program the activity and signaling pathways of immune cells and sex steroid hormones in infants [76], both of which have important implications for sex differences in the capacity to cope with infections and the later development of inflammatory conditions and autoimmune disorders [84,85]. Additional work is needed to understand how prenatal DEHP exposure contributes to developmental immunotoxicity [80,81] and the biological (e.g., immunological, epigenetic) mechanisms that transmit risk in young girls and boys.…”
Section: Discussionmentioning
confidence: 99%
“…The results should encourage translational research from the observations we made in a real human population to the clinic and the laboratory ( Porta et al, 2014b ); that is, they can inspire clinical and laboratory research on mechanisms through which the environmental agents we studied may influence immune processes and contribute to general immunomodulation, hypersensitivity, inappropriate enhancement, immunosuppression, autoimmunity, viral entry and recognition, endocrine and metabolic disruption, glucose metabolism, cytokine production, inflammation, host susceptibility to infection and disease severity, epigenetic modification of immunomodulatory genes, and immunologic memory pathways, among others ( Weaver et al, 2022 ; Gore et al, 2015 ; Dietert et al, 2010 ; Germolec et al, 2022 ; International Programme on Chemical Safety, 2012 ; Alper and Sawyer, 2019 ; Bulka et al, 2022 ; Kostoff et al, 2023 ; Clerbaux et al, 2022 ; Courtin and Vineis, 2021 ). Several of these pathways overlap with those involved in the host response to the SARS-CoV-2 virus and may contribute to explain the associations we report.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous environmental chemicals are immunoactive and cause a range of adverse clinical effects ( Karachaliou et al, 2021 ; Kogevinas et al, 2021 ; Weaver et al, 2022 ; Gore et al, 2015 ; Dietert et al, 2010 ; Germolec et al, 2022 ; International Programme on Chemical Safety, 2012 ; Alper and Sawyer, 2019 ; Bulka et al, 2022 ; Franza and Cianci, 2021 ). It has been hypothesized that some agents, including persistent organic pollutants (POPs) and chemical elements, might also affect the risk of COVID-19 across multiple systems and pathways ( Weaver et al, 2022 ; Bulka et al, 2022 ; Rayasam et al, 2022 ; Kostoff et al, 2023 ; Clerbaux et al, 2022 ). However, uncertainties abound, particularly for the so-called rare earth elements and other chemical elements (including some metals, essential trace elements, and minority elements).…”
Section: Introductionmentioning
confidence: 99%
“… 12 14 The negative impact of chronic inflammation on vaccines efficacy has been seen mainly in the elderly and in chronic inflammatory conditions. 15 In relation to COVID-19, air pollutants may alter several immune pathways also mediated by epigenetic regulation 16 that are involved in the development and severity of the disease and could also affect vaccine efficacy.…”
Section: Introductionmentioning
confidence: 99%